Deteksi Dini dan Tata Laksana Melanonychia: Tinjauan Sistematik - Ambarita, Wiryanti; Fuadi, Anwar (PT Kalbe Farma Tbk., 2024)
Introduction: Melanonychia is brown or black pigmentation of the nail plate caused by melanin accumulation. Melanonychia is a common cause of nail discoloration that can progress to malignant melanoma. Methods: A literature review on scientific databases PubMed and Science Direct. The keywords used were “melanonychia”, “early detection”, and “treatment approach”. The inclusion criteria were all scientific articles on early detection methods and approaches to melanonychia management. Results: The initial search obtained 125 scientific articles relevant to the specified keywords. Screening the title and abstract of the study resulted in 45 articles that were downloaded and underwent full-text screening. Five articles met the inclusion criteria, and qualitative analysis was carried out. Conclusion: Early detection of melanonychia is very important to prevent complications from malignant melanoma. Delayed diagnosis occurs due to low patient awareness of melanonychia lesions and their prognosis.